Дослідження мотивації у соціологічних теоріях електоральної поведінки - Вільчинська, І.Ю. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируются основные аспекты изучения мотивации избирателей в социологических теориях. Большое внимание уделяется исследованиям в рамках теорий социального статуса (П. Лазарсфельд), парадигмы раскола (С. Липсет, С. Роккан), а также идеологическим и институциональным факторам электорального поведения. This article analyzes the main aspects of the research motivation of voters in Sociological Theory. The greatest attention is paid to research within the theory of social status (P. Lazarsfeld) paradigm split (S. Lipset, S. Rokkan), as well as ideological and institutional factors electoral behavior.